2011
DOI: 10.1007/s11104-011-1004-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of beech (Fagus sylvatica), ash (Fraxinus excelsior) and lime (Tilia spec.) on soil chemical properties in a mixed deciduous forest

Abstract: Aims We aimed to determine the influence of the distribution of different broadleaved tree species on soil chemical properties in a mature deciduous forest in Central Germany.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
104
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(138 citation statements)
references
References 53 publications
23
104
3
1
Order By: Relevance
“…They concluded that the higher the N content the greater the CO 2 efflux produced. Langenbruch et al (2012) showed in the same forest that ash litter has a higher N content than beech, which would support our findings for dark respiration with regard to the results of Ryan et al (1996). Therefore, our study leads to the conclusion that ash respires most of the assimilated C directly in the leaves, presumably at night, whereas beech allocates more of the assimilated C belowground.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…They concluded that the higher the N content the greater the CO 2 efflux produced. Langenbruch et al (2012) showed in the same forest that ash litter has a higher N content than beech, which would support our findings for dark respiration with regard to the results of Ryan et al (1996). Therefore, our study leads to the conclusion that ash respires most of the assimilated C directly in the leaves, presumably at night, whereas beech allocates more of the assimilated C belowground.…”
Section: Discussionsupporting
confidence: 90%
“…Trees like beech accumulate more C org in the forest floor and less C org in the mineral soil compared to ash (Langenbruch et al, 2012). This property of beech was mainly attributed to the high C:N and lignin:N ratio in litter, which slows decomposition (Guckland et al, 2009;Kooijman and Cammeraat, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…At the Michigan sites, Davis [20] found litter N concentrations in black ash to be greater than non-ash (i.e., red maple and yellow birch) species. Other studies have also found high concentrations of N in ash litter, leading to high turnover rates of ash litter and greater soil N availability compared to non-ash species [21,22]. Nisbet et al [23] considered the reduction of ecosystem N following EAB invasion of ash riparian forests and speculated that (1) the terrestrial ecosystem could have dramatic changes in net primary production and species composition, and (2) lower amounts of N transport to streams could have cascading effects up the streams' trophic levels and lead to a lowering of stream productivity.…”
Section: Changes In Nitrogen (N) and Carbon (C) Cycling Resulting Fromentioning
confidence: 96%
“…Its leaves are rich in mineral elements, and their fast decomposition has a positive and significant impact on the quality of the soil nutrient status, especially in nutrient-poor sites [18,19,35,99]. In comparison with Fagus, Tilia litter has lower C/N and lignin/N ratios, which makes decomposition faster, and contains more base cations [100]. Litter in a Tilia stand has a higher pH, base saturation, and nutrient stock than that in a Fagus stand [101].…”
Section: Mixed Stands and Ecosystem Servicesmentioning
confidence: 99%